Management of Chronic Hepatic Itch - Düll, Miriam; Kremer, Andreas (Dermatologic Clinics, 2018)
Hepatic itch remains among the most agonizing symptoms for affected patients and a major clinical challenge for physicians. Pruritus may occur in almost all liver diseases, particularly those with cholestatic features. Hepatic itch arises irrespective of the severity of the underlying liver disease or extent of cholestasis. Antihistamines are ineffective in hepatic itch. Therapeutic recommendations consist of a guideline-based stepwise approach, starting with the anion exchange resin cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors are promising future treatment options. Experimental and invasive procedures should be reserved for refractory pruritus.
EVALuna2:35154